Systematics of the dung beetle tribe Sisyphini Mulsant (Scarabaeidae: Scarabaeinae) inferred from a molecular phylogeny and biogeography of southern African species. (27th June 2019) - Daniel, Gimo M.; Sole, Catherine L.; Davis, Adrian L.V.; Strümpher, Werner P.; Scholtz, Clarke H.
Abstract: The tribe Sisyphini Mulsant was recently redefined following the transfer of the endemic southern African genus Epirinus Dejean from the polyphyletic tribe Deltochilini Lacordaire. A molecular phylogeny of the southern African members of Sisyphini supports Epirinus as sister to Sisyphus Latreille and recovered three major clades in Sisyphus classified here as subgenera Sisyphus ( Neosisyphus Müller) stat. rev., Sisyphus ( Parasisyphus Barbero, Palestrini & Zunino) stat.n. and Sisyphus ( Sisyphus ) stat.n. A molecular clock analysis suggests that Sisyphus and Epirinus diverged from their last common ancestor during the Lower to Middle Oligocene ( c . 29.37 Ma). Biogeographical analysis indicated that southern African Sisyphus species are centred in the east and northeast in Highveld grassland and warmer savannah regions. By contrast, Epirinus species are largely restricted to the southwest and southeast in the cooler winter and bimodal rainfall regions plus arid highland Karoo and Highveld grasslands. Based on morphological and biogeographical differences between Epirinus and Sisyphus, we propose that the monogeneric Epirinus be placed in its own tribe, Epirinini van Lansberge stat. rev. Abstract : The phylogeny infers paraphyly of Sisyphus in respect to Neosisyphus and Parasisyphus . Therefore, Sisyphus is divided into three subgenera; Parasisyphus stat.n., Sisyphus and Neosisyphus stat. rev. Sisyphus are centred to the east and northeast in warmer savannah regions. By contrast, Epirinus are largely restricted to the southwest and southeast in the cooler winter and bimodal rainfall regions. Epirinus placed in its own tribe, Epirinini stat. rev. Therefore, we revalidate the concept of the tribe Sisyphini in its stricto sensu.